Nicotine metabolite ratio predicts smoking topography and carcinogen biomarker level - Strasser, Andrew A. (2011)
BACKGROUND: Variability in smoking behavior is partly attributable to heritable individual differences in nicotine clearance rates. This can be assessed as the ratio of the metabolites cotinine (COT) and 3'-hydroxycotinine (3HC) (referred to as the nicotine metabolism ratio, NMR). We hypothesized that faster NMR would be associated with greater cigarette puff volume and higher levels of total NNAL, a carcinogen biomarker. METHODS: Current smokers (n=109) smoked one of their preferred brand cigarettes through a smoking topography device and provided specimens for NMR and total NNAL assays. RESULTS: Faster nicotine metabolizers (third and fourth quartiles versus first quartile) based on the NMR exhibited significantly greater total puff volume and total NNAL; the total puff volume by daily cigarette consumption interaction was a significant predictor of total NNAL level. CONCLUSION: A heritable biomarker of nicotine clearance predicts total cigarette puff volume and total NNAL. IMPACT: If validated, the NMR could contribute to smoking risk assessment in epidemiological studies and potentially in clinical practice.